Motivating Students & Teachers In Higher Education With Reference To Pandemic Situations - Dr Kiran Kumar Thoti, Mr. Dhanikonda Rama Lingeswara Sarma, Mr. GLN Sravan Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Study is focused on the student learning skills and continuous the gaining the knowledge and updating the learning skill both by the faculty and students. The teachers had to play as Facilitator, Manager and Designer of Learning to the Students. The study chose the motivation theories from the organization behavior that applied in our students learning activities in COVID 19. The Teaching and Learning practices was change due to the pandemic condition in the global, COVID 19 take over any options and off line practices in India. The study is focused on the motivation practices for teachers and students to engage them learning and share the learning path.